Cutis Aplasia as a clinical hallmark for the syndrome associated with 19q13.11 deletion: the possible role for UBA2 gene - Melo, Joana B. (2015)
Background: Wide genome screening through array comparative genomic hybridization made possible the recognition of the novel 19q13.11 deletion syndrome. There are very few cases reported with this deletion, but clinically this condition seems to be recognizable by pre and postnatal growth retardation, microcephaly, developmental delay/intellectual disabilities, speech disturbance, hypospadias (in males) and signs of ectodermal dysplasia and cutis aplasia over the posterior occiput. Results: Using oligoarray CGH, a 4.6 Mb deletion in 19q13.11q13.12 was detected in a 23 year old female patient that presented clinical features previously associated with 19q13.11 deletion. Conclusions: Our work reinforces the idea that a region encompassing four zinc finger genes is likely to be responsible for the syndrome, and that the difference in minor clinical manifestation depends on the genes present outside the minimal overlapping region proposed for this syndrome. We also review all cases described in the literature and discuss the correlation between haploinsufficiency of UBA2 gene and cutis aplasia present in the majority of the patients reported, and its importance as a clinical hallmark of 19q13.11 deletion syndrome, when associated with more common features like developmental delay, microcephaly, speech disturbance and hypospadias in males.